Była światłość prawdziwa (J 1,9a) Jezus jako światłość w Prologu czwartej Ewangelii - Sikora, Adam Ryszard (Poznańskie Studia Teologiczne, 2010)
This article aims to „The true light (Jn 1.9a). Jesus as the light in the Prologue of the Fourth Gospel”, was to explain the meaning of the symbol of the light connected with the person of Jesus Christ - the Logos in the Prologue of the Gospel of St John. The analysis of the text helped to establish that the author wanted to show the person o f Logos as a necessary condition of all life, and above all, the supernatural life (Jn 1,4). By revealing the divine life through the Incarnation, whose symbol is a light, he met with extreme hostility, which, however, is unable to destroy him (Jn 1,5). He is the light in an absolute sense (Jn 1,9). No one besides Him can not bestow the light, which in its fullest sense is identified with salvation. Father (John 5,31-32.37-38; 8,16-19), the Holy Spirit (Jn 15,26), the work of Jesus (Jn 5,36,10,25) and John the Baptist (Jn 1,7-8; 19nn) bear witness of His light, that people believed in him and thus have eternal life (Jn 20,31).